Regional Validation Coastal Sea Level Anomaly Estimation from Altimetry Satellite and Tide Gauges Data using Fuzzy Inference System: A Case Study Around Natuna Seas - Permana, Rizki Dimas; Gaol, Jonson Lumban; Irawati, Febri Dwi; Rohman, Tefur Nur; Badri, Rizty Maulida (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
The validation of waveform retracking analyses with Fuzzy Inferences system, which was previously developed to optimize the estimation of sea surface height (SSHs), particularly in coastal locations, is presented in this study. The fuzzy inference system has been tested and validated in the Natuna Sea, Indonesia, where altimetry waveforms varied based on water conditions. Validation was performed by comparing the waveform retracking result of Jason-3 data with in-situ tide gauge data and geoid. The validation of waveform retracking data for sea level anomaly (SLA) estimate against tidal data demonstrates that the waveform retracking with a fuzzy inference system is more accurate than previous approaches. Waveform retracking with fuzzy inference system is able to produce an average temporal correlation of 0.75-0.89 and RMSE between 0.15-0.17 m. The waveform retracking combined with a fuzzy inference system can improve SLA estimation accuracy in nearshore up to 4 km from the coastline. The results indicate that retracking with fuzzy inference system has the potential to be used in other complicated oceans.